Lifetime measurements in 110Cd - Harissopulos, S.; Dewald, A.; Gelberg, A.; von Brentano, P.; Zell, K. O.; Kalfas, C. (HNPS Advances in Nuclear Physics, 2020)
Mean lifetimes for the lowest 6 yrast band members have been measured using the Recoil Distance Doppler Shift technique (RDDS). The data have been analyzed via the Differential Decay Curve Method (DDCM). The transition probabilities deduced from the data for the ground band E2 γ-rays are in rather good agreement with the predictions of the U(5)-limit of interacting boson model-1 (IBM-1).